Symmetric Equivalence of Matrix Polynomials and Isolation of a Common Unital Divisor in Matrix Polynomials - Kuchma, M. I. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We find necessary and sufficient conditions for the existence of common unital divisors with given Smith forms of nonsingular matrix polynomials and common factorization of symmetric matrices over rings of polynomials with involution. We obtain conditions for the symmetric equivalence of such matrices.